1985
DOI: 10.1287/mnsc.31.10.1237
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Trends in Time Series

Abstract: Most time series methods assume that any trend will continue unabated, regardless of the forecast lead time. But recent empirical findings suggest that forecast accuracy can be improved by either damping or ignoring altogether trends which have a low probability of persistence. This paper develops an exponential smoothing model designed to damp erratic trends. The model is tested using the sample of 1,001 time series first analyzed by Makridakis et al. Compared to smoothing models based on a linear trend, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
10

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(157 citation statements)
references
References 2 publications
1
146
0
10
Order By: Relevance
“…Gardner (1985) showed that trend damping improves accuracy for extrapolation models. Gardner's exponential smoothing with damped trends was tested in a study involving the 1,001 series from the M-Competition (Gardner and McKenzie, 1985). Trend damping reduced forecast errors by 10.5% on average over forecast horizons 1-18 when compared with traditional exponential smoothing with a linear trend (Makridakis et al, 1982).…”
Section: Damped Trendmentioning
confidence: 99%
“…Gardner (1985) showed that trend damping improves accuracy for extrapolation models. Gardner's exponential smoothing with damped trends was tested in a study involving the 1,001 series from the M-Competition (Gardner and McKenzie, 1985). Trend damping reduced forecast errors by 10.5% on average over forecast horizons 1-18 when compared with traditional exponential smoothing with a linear trend (Makridakis et al, 1982).…”
Section: Damped Trendmentioning
confidence: 99%
“…Despite its popularity, empirical evidence has shown that the Holt linear forecast function tends to overestimate (Gardner and McKenzie, 1985). In view of this, Gardner and McKenzie (1985) describe how a dampening parameter, φ, can be used within Holt's method to give more control over trend extrapolation. The damped Holt method is presented in expressions (4)-(6).…”
Section: Exponential Smoothing With Additive and Multiplicative Trendsmentioning
confidence: 99%
“…Chatfield and Yar (1988) Makridakis et al, 1982). Another approach is to use a simple linear regression on time to produce initial slope and trend (Gardner and McKenzie, 1985). Our experience is that this can give poor results for series that are notably different to a simple linear trend.…”
Section: Description Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The Management Science articles primarily discussed combining methods, including the role of judgement. Two articles, Gardner and McKenzie (1985) and Collopy and Armstrong (1992), proposed new extrapolative …”
Section: Introductionmentioning
confidence: 99%